Food Industries for People & Planet: A new research agenda - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Through this program, IFPRI will provide evidence-based policy assessments to make agri-food industries and food systems more inclusive in terms of employment and income opportunities, more efficient in meeting the food needs of the growing global population, and more conducive to the promotion of healthy diets and environmentally sound food systems. The FIPP program will address key policy questions through integrated country-, value chain-, and company-specific studies that will look across the wider spectrum of the agri-food industry.